2010
DOI: 10.1186/1471-2148-10-298
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of mutation effects and population size on mutation rate in asexual populations: a simulation study

Abstract: BackgroundIn any natural population, mutation is the primary source of genetic variation required for evolutionary novelty and adaptation. Nevertheless, most mutations, especially those with phenotypic effects, are harmful and are consequently removed by natural selection. For this reason, under natural selection, an organism will evolve to a lower mutation rate. Overall, the action of natural selection on mutation rate is related to population size and mutation effects. Although theoretical work has intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…For example, one study found that under fluctuating environmental conditions (e.g. changes in temperature or oxygen availability), the SPM rate increases until it reaches an intolerable level that leads to extinction (32). Importantly, these models suggest that fitness beyond this threshold declines precipitously (7,31).…”
Section: Somatic Point Mutation Ratementioning
confidence: 99%
“…For example, one study found that under fluctuating environmental conditions (e.g. changes in temperature or oxygen availability), the SPM rate increases until it reaches an intolerable level that leads to extinction (32). Importantly, these models suggest that fitness beyond this threshold declines precipitously (7,31).…”
Section: Somatic Point Mutation Ratementioning
confidence: 99%
“…However, if beneficial mutations are sufficiently strong to offset the effect of deleterious mutations, then U* = s b , where s b is the selection coefficient favoring beneficial mutations (Johnson and Barton 2002). Simulation studies have shown that natural selection can favor higher U when the strength, proportion relative to deleterious mutations, or supply (through changes in population size) of beneficial mutations increases, although this result is dependent on population structure (Jiang et al 2010) and the topology of the fitness landscape (Clune et al 2008). Other studies have shown that selection may favor the maintenance of some level of genetic variability in the population such that long-term evolvability is ensured (Barton 1995;Hayden et al 2011;Wagner 2011).…”
Section: Mutation Rate Evolutionmentioning
confidence: 99%
“…So why does our model produce a different fate where the cooperative trait fully invades the system? This is due to beneficial mutations being more likely to arise and get fixed as the population grows [32,33]. After the initial expansion, a large population of cooperators will have higher frequency of beneficial gene X mutations than the small defector patches.…”
Section: Spatial Segregation Of Social Traits Is Inherently Unstablementioning
confidence: 99%